Association between exposure to cadmium and lead during gestation and adverse birth outcomes in the household air pollution intervention network (HAPIN) trial - Alhassan, Mohamed Adnan, author; Peel, Jennifer, advisor; Clark, Maggie, committee member; Keller, Kayleigh, committee member; Neophytou, Andreas, committee member (Colorado State University. Libraries, 2024)
Low- and middle-income countries (LMICs) are particularly vulnerable to the adverse effects of metal exposure. These countries' rapid industrialization coupled with population growth, result in substantial environmental exposures, which many governments have limited capacity to formally regulate. Even when regulations exist, many governments have a limited capacity to enforce those regulations. Additionally, LMICs bear a disproportionate burden of adverse birth outcomes, including low birth weight and preterm birth, which carry long-term health implications such as increased risk of chronic diseases, developmental delays, and mortality. Several studies have examined the association between metals and adverse birth outcomes such as low birth weight and preterm births. Specifically, despite the low number of studies, cadmium has been consistently linked to lower birth weights, smaller sizes for gestational age, and reduced head circumference. However, the association between lead exposure and birth outcomes shows inconsistent results. This inconsistency in findings, along with the low number of studies overall, especially in LMICs, regarding lead has prompted further investigation in our current study. Here we utilized data from the Household Air Pollution Intervention Network (HAPIN) trial, a randomized controlled trial conducted in rural areas of Guatemala, Peru, Rwanda, and India. The HAPIN trial evaluated the impact of replacing biomass stoves with liquefied petroleum gas stoves on various health outcomes, including infant birth weight among 3200 participants. The participants in the current analysis included pregnant women with a live singleton birth with exposure and birth data (n=2396). Maternal exposure to cadmium and lead were evaluated by analyzing dried blood spots using inductively coupled mass spectrometry. Blood spots were collected at baseline (9 - <20 weeks gestational age) and 32-36 weeks gestational age; we also evaluated the average of these two measurements. Birth weight was measured using a digital infant scale, with low birth weight defined as <2500 grams, and gestational age at birth was determined using screening data and ultrasonography, with preterm birth defined as <37 weeks. We utilized linear regression for birth weight and gestational age, logistic regression for dichotomous low birth weight, and Cox proportional hazards model for preterm birth. The models accounted for infant sex, maternal age, nulliparity, body mass index, maternal hemoglobin, mother's dietary diversity, food insecurity, tobacco smoking in the household, and study arm. We assessed effect modification by study location, sex, and study arm by including an interaction term. In sensitivity analyses, we included study location, household assets, maternal education in the models; replaced values below the limits of detection (LOD) with LOD/√2, and evaluated metal concentrations standardized by potassium levels. We also excluded maternal hemoglobin from the main model. The mean birth weight was 3,020 (standard deviation [SD]=445.5) grams, and 10.3% of all births were classified as low birth weight. The mean gestational age was 39.5 weeks (SD=1.7 weeks), and 5.2% of the births were preterm. The median lead concentration across the time points was 1.4 μg/dL (IQR: 0.9 – 2.2 μg/dL), and the median cadmium concentration was 1.0 ng/mL (IQR: 0.7 – 1.4 ng/mL), values comparable to those found in other studies. Overall, the results did not indicate a consistent or strong association between lead or cadmium and adverse birth outcomes. Baseline cadmium levels showed a modest increase in the odds ratio for low birth weight (OR per IQR increase: 1.2, 95% CI: 0.97 to 1.47). Sensitivity analyses closely aligned with the main findings. All the results for effect modification did not indicate differences in the strata. The study found a suggestive, but inconsistent evidence between exposure to cadmium and low birth weight. This study has some limitations. There is potential for non-differential measurement error due to the hematocrit effect, which alters the estimated spot volume based on participants' hematocrit levels. A sensitivity analysis using potassium standardized metal concentrations partially addressed this, but individual hematocrit variability can still bias the observed association towards the null, with a moderate magnitude. The probability of the bias is moderate. The chromatographic effect, which can cause variations in concentration due to the interaction between blood and the analyte with the filter paper, was also partially addressed using internal standards, blanks, calibration samples, quality controls, and reference materials. This potential bias is of low probability and magnitude, biasing the observed association toward the null. Confounding bias was considered a concern due to incomplete adjustment for covariates like seasonal variation, which can affect metal exposure and birth outcomes. Sensitivity analyses supported the main model findings, suggesting a low probability and magnitude of confounding bias, which could bias the observed association towards or away from the null. Despite residual confounding concerns linked to socio-economic indicators like assets and diet diversity, the sensitivity analyses did not deviate from the main model findings, indicating a small probability and magnitude of the bias, which would bias the observed association in either direction. The study had several strengths including a large sample size compared to previous studies, especially those in LMICs and it was conducted in three distinct rural LMIC settings, which, to the best of our knowledge, had not been done before. This study's strength lies in its large sample size of 2,152 participants with complete data, enhancing its statistical robustness and addressing the common issue of small sample sizes and missing data in prior LMIC research. Additionally, its unique examination across three distinct rural LMIC settings provides valuable insights into the regional variations affecting the outcomes studied. Future steps include using whole blood samples instead of dried blood spots (DBS) and measuring exposure at multiple time points, particularly at birth via the umbilical cord, could yield more accurate concentrations. It is also recommended that subsequent studies employ better socio-economic indicators to reduce residual confounding effects. Expanding the geographical scope of the study to include a broader range of urban areas within the HAPIN countries would improve the generalizability of the findings. Additionally, future research should consider analyzing the effects of metal mixtures to better replicate real-world environmental conditions and interactions. The results are generally consistent with existing limited data indicating no evidence of an association between lead and adverse birth outcomes and a potential association between higher cadmium exposure during pregnancy with increased risk of low birth weight.
Keywords: epidemiology; metals; HAPIN; birth